2007
DOI: 10.1007/s00586-006-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

Total lumbar disc replacement in athletes: clinical results, return to sport and athletic performance

Abstract: Despite the increasing popularity of total lumbar disc replacement (TDR) in predominantly young and active patients, no previous study has addressed possibilities, limitations and potential risks regarding athletic performance following TDR. Mechanical concerns remain and the implant's resilience as regards its load-bearing capacity during sporting activities is unknown. Thirty-nine athletic patients fulfilled the inclusion criteria for this study. These patients participated in a large variety of different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 61 publications
3
39
0
1
Order By: Relevance
“…Despite this, he was able to return to full duty 22 weeks after his initial surgery. This is comparable with the experience reported by Siepe et al 19 who reviewed data obtained after lumbar arthroplasty in athletes. In their series of 39 athletes, they identified that peak performance was reached at 5.2 months after surgery, with 37 (94.9%) of the 39 resuming their previous sporting activity.…”
Section: Lumbar Spine: Performance Statussupporting
confidence: 91%
See 1 more Smart Citation
“…Despite this, he was able to return to full duty 22 weeks after his initial surgery. This is comparable with the experience reported by Siepe et al 19 who reviewed data obtained after lumbar arthroplasty in athletes. In their series of 39 athletes, they identified that peak performance was reached at 5.2 months after surgery, with 37 (94.9%) of the 39 resuming their previous sporting activity.…”
Section: Lumbar Spine: Performance Statussupporting
confidence: 91%
“…10,19,21 The magnitude of these forces remains largely unknown. This creates a difficulty in predicting the behavior of a modular implant, such as the ProDisc, under such conditions.…”
mentioning
confidence: 99%
“…The reasons for sacroiliac joint pain following TDR remain unknown. A variety of recently published studies have reported low ROM-values [28,37,59]. The pathomechanism of postoperative ISJ pain in these patients may therefore be similar to that of lumbosacral fusion procedures [29,42,43].…”
Section: Diagnostic Challengesmentioning
confidence: 71%
“…Despite motion preservation in the majority of cases, a variety of recently published studies have reported low flexion/extension ROM-values in a considerable number of cases with unknown consequences [28,37,59]. Furthermore, implant positioning and disc-/implant-height have been shown to influence and increase post-operative segmental lordosis which may ultimately lead to a subluxation of the facet joints (Fig.…”
Section: Radiological Studiesmentioning
confidence: 99%
“…Lumbar total disc replacement · Meta-analysis · Short-and long-term results · Level of evidence Die Ergebnisse der prospektiven Studien bezüglich Patientenzufriedenheit, Reduktion der individuellen Beeinträch-tigungen (VAS und ODI) sind konsistent signifikant gebessert, wobei monosegmentale Versorgungen klinisch signifikant bessere Ergebnisse erzielen als bisegmentale Versorgungen mit den besten Resultaten bei L4/L5 [39]. Die Arbeitsfä-higkeit konnte innerhalb von 24 Monaten deutlich gesteigert werden [3,4,5,8,10,27,40,42,45] und auch die Sportfähig-keit bis hin zum Leistungssport ist über-wiegend erreichbar [40].…”
Section: Introductionunclassified